Data Mining: a Three-Step of Real-Time Audit Paradigm - Anindyo Widhoyoko, Samuel; ., Sasmoko; Biantara, Dheny; Sugiarto, Bambang (International Journal of Engineering and Technology, 2018)
One problem in business is the aspect of reporting through the process of financial audit. The problem with conventional audit is highlighted in this research through literature review of Statement of Auditing Standards (SAS) regarding to the issues of (1) risk assessment, (2) sampling methods, and (3) going concern analysis. This research further describes all these issues in the light of efficient audit process. The method used is exploratory, engaging comprehensive literature review from the perspectives of forensic accounting and information system. The output is to build a three-step financial audit paradigm embedding (1) exploratory data analysis and descriptive modelling in risk assessment, (2) predictive and association analysis in sampling, and (3) grounded professional judgement in going concern analysis.Â Â
Keywords: Financial Audit; Real-Time Management; Risk Assessment; Audit Sampling; Information System; Data Mining; Fraud; Audit Efficiency.